1993
DOI: 10.1002/bip.360330106
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of restricted rotational diffusion of fluorescent lipids in supported planar phospholipid monolayers using angle‐dependent polarized fluorescence photobleaching recovery

Abstract: A theory describing the shapes of polarized fluorescence photobleaching recovery (PFPR) curves for a population of fluorophores undergoing restricted rotational diffusion in two-dimensional systems such as planar membranes has been developed. In this model, restricted rotational diffusion of the fluorophores is described by using reflective boundary conditions, in which the fluorophores are assumed to diffuse freely but only within an angular space of width 2 omega. The magnitude and apparent rate of the PFPR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…Fit parameters were constrained (Eq. 14) by using the steady-state anisotropy of 0.19 (data not shown). Considering the uncertainties about a randomly oriented fraction (Axelrod, 1979) and a collective lipid tilt and/or wobbling motion (discussed in Timbs and Thompson, 1993), there is clearly reasonable agreement with the previous studies.…”
Section: Resultssupporting
confidence: 89%
“…Fit parameters were constrained (Eq. 14) by using the steady-state anisotropy of 0.19 (data not shown). Considering the uncertainties about a randomly oriented fraction (Axelrod, 1979) and a collective lipid tilt and/or wobbling motion (discussed in Timbs and Thompson, 1993), there is clearly reasonable agreement with the previous studies.…”
Section: Resultssupporting
confidence: 89%
“…The molecular rotation about a central axis was described by a Gaussian distribution of rotation angles of mean 0 and width, 2 ϭ 2D rot t (Chandrasekhar, 1943), characterized by a rotational diffusion constant, D rot , and the time between absorption and emission of a photon, t. It was further assumed that the rotation could take place only about the membrane normal, i.e., in one dimension. This assumption is rationalized by former findings, which showed that Ͼ88% of such fluorophores align their transition dipole moments perpendicular to the membrane (Axelrod, 1979;Lieberherr et al, 1987;Timbs and Thompson, 1993). An initial decrease in the anisotropy due to a differ- ence in the direction of the transition dipole moments in absorption and emission, respectively, was neglected because of the high measured anisotropy here in DPPC membranes and that found in other references reporting the anisotropy of the fluorophores in viscous media (Timbs and Thompson, 1990;Schaffer et al, 1999).…”
Section: Resultssupporting
confidence: 71%
“…From the latter values, a two-dimensional anisotropy, r ϭ (I p Ϫ I s )/(I p ϩ I s ), of 0.37 Ϯ 0.07 was determined. The twodimensional anisotropy has been taken here because it is known for fluorophores like rhodamines that they orient with their molecular plane parallel to the surface of a membrane (Axelrod, 1979;Lieberherr et al, 1987;Timbs and Thompson, 1993). From the definition of the anisotropy given above, the mean two-dimensional anisotropy on linear excitation, for a molecule rotating slowly with respect to its excited-state lifetime (a few nanoseconds) but fast with respect to the total time of observation (10 ms here), is r ϭ 0.5.…”
Section: Methodsmentioning
confidence: 99%